Dynamic Changes in the Microbiome and Mucosal Immune Microenvironment of the Lower Respiratory Tract by Influenza Virus Infection - Gu, Liming; Deng, Huixiong; Ren, Zhihui; Zhao, Ying; Yu, Shun; Guo, Yingzhu; Dai, Jianping; Chen, Xiaoxuan; Li, Kangsheng; Li, Rui; Wang, Gefei (Frontiers in Microbiology, 2019)
Influenza is a major public health concern, and the high mortality rate is largely attributed to secondary bacterial infections. There are several mechanisms through which the virus increases host susceptibility to bacterial colonization, but the micro-environment in lower respiratory tract (LRT) of host, infected with influenza virus, is unclear. To this end, we analyzed the LRT microbiome, transcriptome of lung and metabolome of bronchoalveolar lavage fluid (BALF) in mice inoculated intra-nasally with H1N1 to simulate human influenza, and we observed significant changes in the composition of microbial community and species diversity in the acute (7 days post inoculation or dpi), convalescent (14 dpi) and the recovery (28 dpi) periods. The dominant bacterial class shifted from Alphaproteobacteria to Gammaproteobacteria and Actinobacteria in the infected mice, with a significant increase in the relative abundance of anaerobes and facultative anaerobes like Streptococcus and Staphylococcus. The dysbiosis in the LRT of infected mice was not normalized even in the recovery phase of the infection. In addition, the infected lung transcriptome showed significant differences in the expression levels of genes associated with bacterial infection and immune responses. Finally, the influenza virus infection also resulted in significant changes in the metabolome of the bronchoalveolar lavage fluid (BALF). These alterations in the microbiome, transcriptome and metabolome of infected lungs were not only appeared at the acute period, but also observed at the recovery period. Furthermore, the infection of influenza virus induced a long-term effect in LRT micro-environmental homeostasis, which may give a chance for the invasion of potential pathogens.